Bjørn Staal’s Entangled Aesthetics: The Intersection of Quantum Mechanics, Blockchain, and Contemporary Art - Assis, Paulo de (2024)
Analysis of a multimedia installation.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music